CLUSTERING VALUE OF SMAN 1 SUMENEP STUDENT REPORTS USING K-MEANS METHOD - Fanni Silvana; Mariska Regina (IJCONSIST JOURNALS, 2022)
Education is the basis for the formation of human character. There are two types of education in schools, namely formal education and extracurricular education. Extracurricular activities are additional activities that are usually carried out outside school hours. The existence of this extracurricular activity helps students to develop their talents and potential. This research was conducted at SMA Negeri 1 Sumenep which facilitates 23 extracurricular activities for its students. Based on these activities, there are 72 students as a dataset. This study determines the grouping of extracurricular selection using the K-Means Clustering method. This method is expected to provide an understanding of the grouping of students according to their interests and potential based on the extracurricular options they choose. The results obtained are 3 clusters, namely the category of bad, good and very good with a value of 76.12 each. 85.25 and 79.43. Based on the three clusters formed with centroid points C0 (3.8, 77.9), C1 (1.4, 87.4), and C2 (1.8, 82.4).